Botanical Literacy and Learning Media: What Can Scopus AI Tell Us? (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2025)
Botanical literacy, crucial for addressing biodiversity and sustainability challenges, is declining due to ineffective traditional learning media. This review utilizes Scopus AI to analyze trends in botanical literacy research and the role of innovative learning media. Key insights include: (1) traditional textbooks are insufficient, while emerging tools such as augmented reality (AR) and interactive games enhance engagement and comprehension; (2) research is concentrated on assessment methods, learning tools, and educational approaches, with immersive technologies addressing Plant Awareness Disparity (PAD) and bridging gaps in experiential learning; and (3) technologies like virtual field trips and AI applications are transforming botanical education by promoting ecological awareness and higher-order thinking. The review emphasizes the need for technology-integrated, student-centered pedagogies and identifies gaps in AI-driven research synthesis. Future directions include longitudinal studies on AR/VR effectiveness, AI-customized tools, teacher training, and cross-cultural assessments. By synthesizing Scopus AI’s data-driven insights with manual analysis, this review provides a roadmap for developing evidence-based learning media that cultivate plant-literate generations capable of addressing global environmental challenges.